Kajian Hukum Terhadap Pengembangan Fintech Syariah Di Indonesia - Virdi, Irham (UI Scholars Hub, 2022)
In meeting the needs of today's financial services that are entering the era of digitalization, a service is needed following the developing financial technology. The existence of Islamic financial technology (fintech) is an alternative to fulfill the needs of financial services at this time. As one of the countries with the largest Muslim population in the world, Islamic fintech can be an option and has great potential because it follows current technological developments and sharia. However, the implementation of Islamic fintech faces various obstacles, including its regulation, the obligation of DPS, technical implementation, and human resources. For this reason, a study was conducted to analyze: 1) the regulation of sharia peer-to-peer lending in supporting the development of Sharia fintech in Indonesia; and 2) the problems faced by Sharia fintech in Indonesia and efforts to overcome them. The research results on the regulation of Sharia Principles still need to be visible in the regulations for implementing Information technology-based Money Lending and Borrowing services. There must be literacy about Sharia fintech to the public so that Sharia fintech can grow.